1991
DOI: 10.1200/jco.1991.9.7.1113
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of prognosis in primary breast cancer by detection of a high molecular weight mucin-like antigen using monoclonal antibodies DF3, F36/22, and CU18: a Cancer and Leukemia Group B study.

Abstract: Three monoclonal antibodies (MAbs) (DF3, F36/22, CU18) were used to monitor expression of distinct epitopes present within a family of mucin-like, breast carcinoma-associated molecules. Primary tumor specimens from more than 190 stage II breast cancer patients were evaluated for expression of the high molecular weight antigens. With a median follow-up of 6 years, patients whose tumors exhibited high immunoperoxidase staining scores (greater than 50% positive cells) with MAb DF3 had a superior disease-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 32 publications
1
37
2
Order By: Relevance
“…46 The associations between cytoplasmic expression and poor outcome and between apical expression and favourable outcome have also, been reported. 47,48 Other studies, however, found no association between either level of expression or the site of expression and outcome. [49][50][51] In our series, MUC2 was expressed with a very high frequency in mucinous carcinomas compared with other tumour types as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…46 The associations between cytoplasmic expression and poor outcome and between apical expression and favourable outcome have also, been reported. 47,48 Other studies, however, found no association between either level of expression or the site of expression and outcome. [49][50][51] In our series, MUC2 was expressed with a very high frequency in mucinous carcinomas compared with other tumour types as previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…CA15-3 is a mucin belonging to a large family of glycoprotein encoded by the MUC1 gene (Hayes et al, 1991) that are heterogeneously expressed on the apical surface of normal epithelial cell types, including those of the breast (Hayes et al, 1991). CA15-3 is elevated in breast DOI:http://dx.doi.org/10.7314/APJCP.2012.13.3.857 Serum CA15-3 in Benign and Malignant Breast Lesions cancer patients with distant metastases and recurrences (Shering et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] Intercellular/circumferential labeling was associated with a high incidence of lymph node metastases as well. 28 Interestingly, none of these labeling patterns (intracytoplasmic or intercellular) is seen in invasive micropapillary carcinoma despite the high propensity of the tumor for lymph node metastases and its poor prognosis. Our finding in invasive micropapillary carcinoma, however, provides further evidence that any aberrant localization of MUC1 in the tumor cells (intracytoplasmic, intercellular, or basal) confers to the tumor a worse prognosis and possibly a high propensity to disseminate.…”
Section: Muc1 In Invasive Micropapillary Carcinoma H Nassar Et Almentioning
confidence: 99%